Maternal complications in childbirth and the puerperium in patients with previous cesarean section, attended in a level III hospital Cusco - 2018 - Vera-Castillo, Briyithee Milagros (2022)
Introduction: The management of pregnant women with previous cesarean section is always a subject of debate, especially due to the risks and complications that an iterative surgical intervention entails, the management of attempting a vaginal delivery after cesarean section is recommended and convenient, however, it is important be on the lookout for complications. Objective: To determine maternal complications in childbirth and the puerperium in patients with previous cesarean section, attended at the Hospital Antonio Lorena Cusco 2018. Materials and Methods: Descriptive, cross-sectional study, with a quantitative, retrospective approach, the sample was of 372 pregnant women where 186 had Previous cesarean section and 186 no, between January and December 2018, being the document review technique of medical records in a data collection sheet validated by experts, the data were digitized in SPSS version 23 for data analysis. Results: The pregnant women with a previous cesarean section were between 18-34 years old in 60% and those who did not have a previous cesarean section were 35 years or older in 46%, they are multigesta 46% and 57% respectively; with an intergenetic period of 2-5 years 68% and 73%, culminated in vaginal delivery in 55% and 77%; In those who underwent caesarean section, the diagnosis was hypertensive disorder 19% and bleeding in the second half of pregnancy 15%. Maternal complications during delivery were contractility dystocia, 19% in pregnant women with previous cesarean section and 22% in pregnant women without previous cesarean section, 19% and 12% presented intrapartum hemorrhage; In the puerperium, anemia was found due to losses 25% and 17%, postpartum hemorrhage 17% and 12%. Conclusions: The maternal characteristics and those of the previous cesarean section influence the probability of having a subsequent vaginal delivery and it is evidenced that the complications do not differ due to the history of cesarean section, which warrants considering the choice of vaginal delivery in pregnant women with a previous cesarean section.